Validation of a Simple and Rapid Method for Assessment of Intracellular Bacterial Asparaginase: Validation of a Simple Method for Assessment of Bacterial Asparaginase - Mahmood Barati; Maryam Tabarzad; Hossein Safarpour; Ali Ghanbariasad; Omar Ghaderi (Iranian Journal of Pharmaceutical Sciences, 2016)
L-Asparaginase has remarkable properties which make it useful in dual pharmaceutical and food industries.In this study, simple and advantageous methods have been validated for rapid and precise determination of intracellular L-Asparaginasein bacterial species. A suspension of bacterial cells was used instead of cell extract and incubated by substrate (asparagine) after simple wash and centrifugation steps. Due to loss of enzyme activity which could be caused by cell distruption methods such as sonication or enzymatic treatment, cell suspension was used instead of the cell extract. Thus, this method not only is cost effective but also speeds up the screening process and leasd to higher measurement accuracy. To validate this method, two species of bacteria; E.coli ATCC 8739 and Halomonas H28 were used. After cultivation, the cells were harvested and washed. Then, 5 serial dilutions were prepared from each bacterium, and the asparaginase activity in each of them was measured by methods including sonication, enzymatic lyses, and the cell suspension. The results have showed that the changes in asparaginase activity in all 5 serial dilutions are linear and there is good agreement between the sonication and the cell suspension methods. Also, it was shown that activities measured by the enzymatic method were significantly higher than the other two methods.